2020
DOI: 10.20945/2359-3997000000244
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroid injection of dexamethasone inhibits Th2 cells in Graves’ disease

Abstract: Objective: Intrathyroid injection of dexamethasone (IID) was used for decrease the relapse rate of hyperthyroidism in the treatment of Graves' disease (GD), but the mechanism is still unclear. We aimed to explore the effect of IID on T help (Th)1/Th2 cells and their chemokine in patients with GD. Subjects and methods: A total of 42 patients with GD who were euthyroidism by methimazole were randomly divided into IID group (n = 20) and control group (n = 22). Thyroid function and associated antibody, Th1/Th2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similar to other autoimmune diseases, the pathogenesis of GD is related to the imbalance of related cytokines in the body [7]. e CXC chemokine 13 (CXCL-13) is a proin ammatory chemokine derived from stromal cells, which has a strong proinammatory capacity and can bind to its receptor CXCR-5, playing an important role in the regulation, aggregation, and migration of B lymphocytes proliferation and di erentiation [8,9]. Retinol-binding protein-4 (RBP-4) is a transporter protein distributed in blood, urine, and other body fluids, which plays an important role in fat metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other autoimmune diseases, the pathogenesis of GD is related to the imbalance of related cytokines in the body [7]. e CXC chemokine 13 (CXCL-13) is a proin ammatory chemokine derived from stromal cells, which has a strong proinammatory capacity and can bind to its receptor CXCR-5, playing an important role in the regulation, aggregation, and migration of B lymphocytes proliferation and di erentiation [8,9]. Retinol-binding protein-4 (RBP-4) is a transporter protein distributed in blood, urine, and other body fluids, which plays an important role in fat metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…This study was remarkable for the histological finding that showed an improvement in histological picture even on the day following injection, which showed a reformation of follicular structure and a reduction in epithelial cells swelling [14]. ISI was proved to inhibit Th2 cells in Graves` disease [15], which may also play a role in SAT pathogenesis [16]. Five cases of painful Hashimoto thyroiditis were successfully treated with injection of triamcinolone [17,18].…”
Section: Side Effectsmentioning
confidence: 99%
“…Dexamethasone (DEX), a synthetic glucocorticoid, is widely used in various clinical departments, including endocrinology, oncology, and respiratory medicine (9)(10)(11). Furthermore, glucocorticoids exert analgesic effects by reducing the secretion of bradykinin and neuropeptides tissues, as well as inhibiting pain signaling in the noxious C-fibers (12,13).…”
Section: Introductionmentioning
confidence: 99%